PENGOLAHAN AIR LIMBAH DOMESTIK DENGAN ANOKSIK-AEROBIK MOVING BED BIOFILM REACTOR (STUDI KASUS: PENYISIHAN AMONIA DAN KARBON DALAM AIR LIMBAH DOMESTIK) - Ningtias, Berliana C.; Moersidik, Setyo S.; Priadi, Cindy R.; Said, Nusa Idaman (Jurnal Air Indonesia, 2015)
Domestic wastewater contains high organic carbon and ammonium concentration which can be treated by moving bed biofilm process. It is a biologycal hybrid between attached and suspended growth process. The purposes of this research were to determine the removal percentage of organic carbon and ammonium concentration in domestic wastewater, and to investigate optimum hydraulic residence time. Experiment was carried out in a laboratory scale to study the combine anoxic and an aerobic reactor condition. The treatment process is preceeded by a 4-week seeding process continued with variation of hydraulic residence time. Based on these results, the removal percentage of COD for each hydraulic residence time of 12, 16, and 20 hours were 75,7%; 83,7%; and 91,0%, the removal percentage of ammonium were 79,4%; 91,0%; and 92,3%. The optimum hydraulic residence time in removing organic carbon and ammonium concentration domestic wastewater using anoxic aerobic MBB is 20 hours. This biological hybrid treatment can be an alternative to remove organic carbon and ammonium in domestic wastewater.Ã‚Â Keyword: domestic wastewater, ammonium removal, organic carbon removal, moving bed biofilm reactor